Analisis dan Implementasi Modul Rekomendasi Fasilitas Kesehatan Terdekat pada Sistem Informasi Dhealth - adi saputra, komang cameng; Anom Cahyadi Putra, I Gst Ngurah (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
The development of the quality of health of a community cannot be separated from the availability of health facilities. With the development of technological information, administration, and services, making health facilities easier. Mobile application development makes it easier for users, to find information about health facilities and administration will be easier by using a mobile application. The development of mobile applications itself is facilitated by the use of react native, a framework used for the development of mobile applications using javascript. To develop applications on two platforms, namely Android and iOS, it can be done in one work with react native. The application of the development of a search module for the nearest hospital using react native can be done using 2 APIs, namely geolocation and Distance Matrix API.